The Distribution of Genus Favia (Oken, 1815) at the Reef Flats of Likupang Kampung Ambong Village Minahasa Utara - . Reskiwati; Laurentius Th. X. Lalamentik; Unstain N.W.J. Rembet (Sam Ratulangi University, 2019)
Six species of Favia were found in this study i.e, Favia pallida (Dana, 1846), Favia speciosa (Dana, 1846), Favia favus (Forskål, 1775), Favia truncatus (Veron, 2000), Favia rotundata (Veron and Pichon, 1977) and Favia matthaii (Vaughan, 1918). The species with the highest percentage of coral cover was Favia pallida (0,386 %). The values of Dominance Index showed that there were no dominant Favia species on Kampung Ambong coral reef flats. Diversity Index (H’) of Favia was 1,47. There are two distribution patterns shown by Favia on Kampung Ambong coral reef flats area, which are clumped and uniformed.Keywords: Favia, Distribution ABSTRAKDalam penelitian ini ditemukan 6 spesies karang genus Favia, yaitu Favia pallida (Dana, 1846), Favia speciosa (Dana, 1846), Favia favus (Forskål, 1775), Favia truncatus (Veron, 2000), Favia rotundata (Veron and Pichon, 1977) dan Favia matthaii (Vaughan, 1918). Spesies dengan persentase tutupan karang tertinggi adalah Favia pallida (0,37 %). Nilai Indeks Dominasi menunjukkan tidak ada spesies karang genus Favia yang dominan pada rataan terumbu Kampung Ambong. Indeks keanekaragaman karang genus Favia menunjukkan nilai H’ = 1,47. Terdapat dua Pola distribusi yang diperoleh dari karang genus Favia di rataan terumbu Kampung Ambong, yaitu mengelompok dan seragam.Kata Kunci : Favia, Distribusi